Hydrological Dynamics of the Congo Basin From Water Surfaces Based on L‐Band Microwave. Issue 2 (4th February 2021) - Fatras, C.; Parrens, M.; Peña Luque, S.; Al Bitar, A.
Abstract: In this study, the hydrological dynamics of the Congo River Basin (CRB) have been analyzed. This is achieved using multiangular and dual‐polarization passive L‐band microwave signal from the Soil Moisture and Ocean Salinity (SMOS) satellite to estimate water surface extent dynamics from 2010 to 2017. The results provide new insights into the poorly characterized wetlands, peatlands, and floodplains dynamics of the CRB. We found that the mean flooded area for the entire CRB is equal to 89, 408 ± 20, 623 km 2 corresponding to 2.39% of the entire basin. The results were compared with three land cover maps (European Space Agency‐Climate Change Initiative [ESA‐CCI], International Geosphere‐Biosphere Programme [IGBP], and Global Surface Water Occurrence [GSWO]) and the SWAMPS global dynamic water surfaces product. More inland waters were detected than the four previous products, except along the rivers. Floods and droughts during the last 10 years were also depicted. The knowledge about the CRB hydrological behavior was improved by analyzing the date of maximum floods, the time lag in days between precipitation, water surface extent, and river water height at the outlet of the nine major Congo subbasin. A lag of 67 ± 3 days between rainfall and inundated areas was found in the Upper Congo ( r  = 0.89). In the Kasai subbasin, no time lag between rainfall and inundation was found ( r  = 0.86). The contribution of each floodplain to the Congo discharge was also evaluated. In the future, the fusion of the current surface waters with water heights from the SWOT mission can provide further information to the water volumes of the CRB floodplains. Plain Language Summary: The Congo River Basin (CRB) has a vast flooded area, that is poorly characterized. We developed new flood extent maps for the CRB based on satellite data in the L‐band spectral band. This enabled an unprecedented insight into water dynamics of the wetlands, peatlands, and floodplains of the CRB through the detection of the dates of maximum floods, the lag with the rainfall peaks, and the duration of floods even in vegetated areas. Key Points: New knowledge of the Congo River Basin hydrology for the last decade through a new temporal and spatial dynamic water surface extent data The water extent in the Congo River Basin ranges from 78, 602 to 99, 225 km 2 between 2011 and 2017 The lags between rainfall and flood in the nine Congo subbasins has a high variability ranging from 0 to 67 days